2018
DOI: 10.1051/matecconf/201815605020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization Nanofillers from Agriculture Waste for Polymer Nanocomposites Reinforcement

Abstract: The current development of the packaging industry is increasing as well as the dependence of non-renewable oil-based materials encouraging researchers to look for alternative polymeric strengthening materials from biomass. Especially used from agricultural waste because it is cheap and widely available in nature and it can be renewed. In this study, agriculture waste used were rice husk and rice husks ash that prepared as organic nanofillers for the development of polymer nanocomposites. XRF analysis showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Aquades, rice husk, and rice husk ash from Aceh Province, Indonesia. The rice husk and rice husk ash prepared followed by Arifin et al, 2018 4 . Nanoparticles from rice husk and rice husk ash after removed moisture content were washed and dried in an oven for overnight.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquades, rice husk, and rice husk ash from Aceh Province, Indonesia. The rice husk and rice husk ash prepared followed by Arifin et al, 2018 4 . Nanoparticles from rice husk and rice husk ash after removed moisture content were washed and dried in an oven for overnight.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…1 Rice husk is a raw material from biological sources such as silica into a new field that is very well developed in Indonesia with nano technology. 2,3 Arifin et al 4 , found that the silica contents of rice husks 82.54% and the rice husk ask 89.84%. The chemical of silica rice husk and rice husk ash in the form of SiO 2.…”
Section: Introductionmentioning
confidence: 98%